Differential and overlapping immune programs regulated by IRF3 and IRF5 in plasmacytoid dendritic cells - Chow, Kwan T. (J Immunol, 2018)
We examined the signaling pathways and cell type-specific responses of interferon regulatory factor (IRF)5, an immune-regulatory transcription factor. We show that the protein kinases IKKα, IKKβ, IKKε and TBK1 each confer IRF5 phosphorylation/dimerization, thus extending the family of IRF5 activator kinases. Among primary human immune cell subsets, we found that IRF5 is most abundant in plasmacytoid dendritic cells (pDCs). Flow cytometric cell imaging revealed that IRF5 is specifically activated by endosomal Toll-like receptor (TLR) signaling. Comparative analyses revealed that IRF3 is activated in pDCs uniquely through RIG-I-like receptor (RLR) signaling. Transcriptomic analyses of pDCs show that the partitioning of TLR7/IRF5 and RLR/IRF3 pathways confers differential gene expression and immune cytokine production in pDCs, linking IRF5 with immune regulatory and proinflammatory gene expression. Thus, TLR7/IRF5 and RLR-IRF3 partitioning serve to polarize pDC response outcome. Strategies to differentially engage IRF signaling pathways should be considered in the design of immunotherapeutic approaches to modulate or polarize the immune response for specific outcome.